Influences of superabsorbent polymer (SAP) on the compressive strength and crack-healing ability of self-compacting concrete containing high-volume ground bottom ash - Siwakorn Chitthawornmanee; Harsimranpreet Kaur; Trinh Nhat Ho Tran; Pattharaphon Chindasiriphan; Pitcha Jongvivatsakul; Weerachart Tangchirapat (Case Studies in Construction Materials)
This study investigated the use of superabsorbent polymers (SAPs) as an internal curing and crack-healing material in self-compacting concrete (SCC) made with high-volume ground bottom ash (GBA). With a total binder content of 600 kg/m3 and a water-to-binder (w/b) ratio of 0.27, ordinary Portland cement (OPC) was replaced with pozzolanic materials by up to 70 % by weight of the binder. The pozzolanic blend comprised high-volume GBA, original fly ash (FA), and nano-silica (NS) in three weight ratios: 70:0:0, 60:10:0, and 58:10:2 (GBA:FA:NS). Additionally, pre-absorption with SAP and a saturated calcium hydroxide (Ca(OH)₂) solution was employed, and the crack-healing ability of SCC with SAP was observed. The results demonstrated that SAP significantly controlled the slump flow and T50 while reducing the required dosage of superplasticizer. However, an increase in SAP content led to a decrease in compressive strength. Reduced water flow rate through the cracked concrete was observed for the first two weeks in SCC mixes containing 0.6–1.8 % of SAP by weight of the binder, decreasing by over 90 % after curing for 28 days. In SCC mixes incorporating SAP saturated with Ca(OH)2, a 98 % reduction in water flow rate was achieved, in addition to a slight increase in compressive strength, due to the additional formation of calcium-silicate-hydrate (CSH) gels and calcium carbonate (CaCO3) precipitation. Furthermore, the inclusion of SAP or SAP saturated with Ca(OH)2 significantly reduced chloride penetration in SCC. Microstructure analysis revealed the presence of crack-healing products including CSH gels and CaCO3 precipitation.